Neuromodulation and a Reconceptualization of Autism Spectrum Disorders: Using the Locus Coeruleus Functioning as an Exemplar - London, Eric B. (Frontiers in Neurology, 2018)
The autistic spectrum disorders (ASD) are a heterogeneous group of developmental disorders. ASD can be reliably diagnosed, however the etiology, pathophysiology and treatment targets remain poorly characterized. Although there are many atypical findings in anatomy, genetics, connectivity and other biologic parameters, there remains no discreet hypothesis to explain the core signs as well as the very frequent comorbidities. Due to this, designing targets for treatments can only be done by assuming each symptom is a result of discreet abnormality which is likely not the case. Neuronal circuity remains a major focus of research however rarely including the fact the functioning of the brain is highly dependent on various systems including the neuromodulatory substances originating in the midbrain. A hypothesis is presented which explores the possibilities of explaining many of the symptoms found in ASD, in terms of inefficient neuromodulation using the functioning of the locus coeruleus and norepinephrine (LC/NE) as exemplars. The basic science of LC/NE is reviewed. Several functions found to be impaired in ASD including learning, attention, sensory processing, emotional regulation, autonomic functioning, adaptive and repetitive behaviors, sleep, language acquisition, initiation, and prompt dependency are examined in terms of the functioning of the LC/NE system. Suggestions about possible treatment directions are explored.